Control and optimal control theories with applications - Burghes, David N.; Graham, Alexander, 1936-; ScienceDirect eBooks (Chichester : Horwood, 2004)
This sound introduction to classical and modern control theory concentrates on fundamental concepts. Employing the minimum of mathematical elaboration, it investigates the many applications of control theory to varied and important present-day problems, e.g. economic growth, resource depletion, disease epidemics, exploited population, and rocket trajectories. An original feature is the amount of space devoted to the important and fascinating subject of optimal control. The work is divided into two parts. Part one deals with the control of linear time-continuous systems, using both transfer function and state-space methods. The ideas of controllability, observability and minimality are discussed in comprehensible fashion. Part two introduces the calculus of variations, followed by analysis of continuous optimal control problems. Each topic is individually introduced and carefully explained with illustrative examples and exercises at the end of each chapter to help and test the reader's understanding. Solutions are provided at the end of the book. Investigates the many applications of control theory to varied and important present-day problemsDeals with the control of linear time-continuous systems, using both transfer function and state-space methodsIntroduces the calculus of variations, followed by analysis of continuous optimal control problems.
CHAPTER 11Bang-bang control11.1 INTRODUCTION; 11.2 PONTRYAGIN'S PRINCIPLE; 11.3 SWITCHING CURVES; 11.4 TRANSVERSALITY CONDITIONS; 11.5 EXTENSION TO THE BOLTZA PROBLEM; PROBLEMS; CHAPTER 12Applications of optimal control; 12.1 INTRODUCTION; 12.2 ECONOMIC GROWTH; 12.3 RESOURCE DEPLETION; 12.4 EXPLOITED POPULATIONS; 12.5 ADVERTISING POLICIES; 12.6 ROCKET TRAJECTORIES; 12.7 SERVO PROBLEM; PROBLEMS; CHAPTER 13Dynamic programming; 13.1 INTRODUCTION; 13.2 ROUTING PROBLEM; 13.3 D.P. NOTATION; 13.4 EXAMPLES; 13.5 BELLMAN'S EQUATION; 13.6 THE MAXIMUM PRINCIPLE; PROBLEMS; APPENDIX 1Partial fractions.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Control theory; MATHEMATICS -- Calculus; MATHEMATICS -- Mathematical Analysis; Control theory; Electronic books